Pharmacokinetic and Toxicological Characterization of Tetrandrine Using in silico ADMET Modelling - Putri Niat Salma Halawa; Poppy Anjelisa Zaitun Hasibuan; Denny Satria (International Journal of Research and Review, 2025)
1. Luan F, He X, Zeng N. Tetrandrine: a review of its anticancer potentials, clinical settings, pharmacokinetics, and drug delivery systems. J Pharm Pharmacol. 2020;72(11):1491-1512. doi:10.1111/jphp.13339. 2. Liu T, Liu X, Li W, Li C, Su Q, Yang J, et al. Tetrandrine, a Chinese plant-derived alkaloid, is a potential candidate for cancer chemotherapy. Oncotarget. 2016;7(26):40800–40815. doi:10.18632/oncotarget.8315 3. Liu T, Li K, Zhang Z, Peng J, Yang J, Law BYK, et al. Tetrandrine inhibits cancer stem cell characteristics and epithelial to mesenchymal transition in triple-negative breast cancer via SOD1/ROS signaling pathway. Am J Chin Med. 2023;51(2):425–444. doi:10.1142/S0192415X23500222 4. Błaszczak E, Miziak P, Odrzywolski A, Baran M, Gumbarewicz E, Stepulak A. Triple-negative breast cancer progression and drug resistance in the context of epithelial–mesenchymal transition. Cancers (Basel). 2025;17(2):228. doi:10.3390/cancers17020228 5. Bhagya N, Prabhu A, Rekha PD, Chandrashekar KR. Combination of tetrandrine and cisplatin synergises cytotoxicity and apoptosis in triple negative breast cancer. Synergy. 2020; 10:100063. doi: 10.1016/j.synres.2020.100063. 6. Mo L, Zhang F, Chen F, Fang Y, Tan W, He J, et al. Progress on structural modification of tetrandrine with wide range of pharmacological activities. Front Pharmacol. 2022; 13:978600. doi:10.3389/fphar.2022.978600. 7. Tang W, Chen J, Zhou J, Ge J, Zhang Y, Li P, et al. Quantitative MALDI imaging of spatial distributions and dynamic changes of tetrandrine in multiple organs of rats. Theranostics. 2019;9(4):932–944. doi:10.7150/thno.30408. 8. Askerova UF. Prediction of acute toxicity for (Z)-3-(2-phenylhydrazinylidene) benzofuran-2(3H)-one and its derivatives for rats using GUSAR program. New Mater Compd Appl. 2023;7(1):50-56. 9. Daina A, Michielin O, Zoete V. SwissADME: A free web tool to evaluate pharmacokinetics, drug-likeness and medicinal chemistry friendliness of small molecules. Sci Rep. 2017; 7:42717. doi:10.1038/srep42717. 10. Dai CL, Xiong HY, Tang LF, Zhang X, Liang YJ, Zeng MS, et al. Tetrandrine achieved plasma concentrations capable of reversing MDR in vitro and had no apparent effect on doxorubicin pharmacokinetics in mice. Cancer Chemother Pharmacol. 2007;60(5):741-750. doi:10.1007/s00280-007-0420-0. 11. Wang F, Xu Y, Li J, Luo C, Wei M, Wu X, et al. Quantitative pulmonary pharmacokinetics of tetrandrine for SARS-CoV-2 repurposing. Front Pharmacol. 2024; 15:1457983. doi:10.3389/fphar.2024.1457983. 12. Jin H, Li L, Zhong D, Liu J, Chen X, Zheng J. Pulmonary toxicity and metabolic activation of tetrandrine in CD-1 mice. Chem Res Toxicol. 2011;24(12):2142–2152. doi:10.1021/tx2003283. 13. Shi JP, Li SX, Ma ZL, Gao AL, Song YJ, Zhang H. Acute and sub-chronic toxicity of tetrandrine in intravenously exposed female BALB/c mice. Chin J Integr Med. 2016;22(12):925-931. doi:10.1007/s11655-015-2303-2. 14. Cai Y, Qi XM, Gong LK, Liu LL, Chen FP, Xiao Y, et al. Tetrandrine-induced apoptosis in rat primary hepatocytes is initiated from mitochondria: Caspases and endonuclease G (Endo G) pathway. Toxicology. 2006;218(1):1-12. doi: 10.1016/j.tox.2005.08.024. 15. Qi XM, Miao LL, Cai Y, Gong LK, Ren J. ROS generated by CYP450, especially CYP2E1, mediate mitochondrial dysfunction induced by tetrandrine in rat hepatocytes. Acta Pharmacol Sin. 2013; 34(9):1229–1236. doi:10.1038/aps.2013.71.